Efficacy of 30% and 38% Silver Diamine Fluoride in Arresting Caries Lesions After Different Application Times: An in Vitro Study - Gabriella Fernandes Rodrigues; Amanda Souza Nunes Monteiro; Ana Lúcia Vollú; Paula Maciel Pires; Aline Saddock de Sá Silva; Ricardo Tadeu Lopes; Branca Heloisa Oliveira; Aline de Almeida Neves; Fernanda Barja-Fidalgo; Andréa Fonseca-Gonçalves (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the efficacy of silver diamine fluoride (SDF) in arresting dentin caries lesions when applied under different concentrations and times. Material and Methods: Forty-two bovine blocks were selected and fixed in 24-well plates. Each well received a mixed bacterial inoculum added to the culture medium with 5% sucrose. The plates were incubated in microaerophilia (7 days) for caries formation, confirmed by micro-CT (M1). SDF was applied over the carious lesions for different times and concentrations (n=6): SDF 30% - immediate removal, 1 minute and 3 minutes; SDF 38%, - immediate removal, 1 minute and 3 minutes. The group without treatment was the control. Then, the samples were again scanned by micro-CT (M2) and submitted to a second cariogenic challenge for 21 days. Then, a final scan was performed (M3). Results: Mean pH at the culture medium and lesion depth were compared using Kruskal-Wallis and Wilcoxon tests. 38% SDF showed the lowest metabolic activity of the biofilm. All 38% groups and 30% 1 and 3 minutes did not show an increase in mean lesion depth comparing M3 with M1. However, only 30% 3 minutes and 38% 1 and 3 minutes showed a significant reduction of lesion depth. Conclusion: The minimum application time of 30% SDF to arrest dentin caries lesion was 1 minute, while 38% SDF arrested with application and immediate removal.